Moderate-Temperature Carbon Capture Using Thermally Pre-Treated Dolomite: A Novel Approach - Iyiade G. Alalade; Javier E. Morales-Mendoza; Alma B. Jasso-Salcedo; Jorge L. Domínguez-Arvizu; Blanca C. Hernández-Majalca; Hammed A. Salami; José L. Bueno-Escobedo; Luz I. Ibarra-Rodriguez; Alejandro López-Ortiz; Virginia H. Collins-Martínez (C)
This study investigates a novel approach to moderate-temperature carbon capture by examining the enhanced performance of thermally pre-treated dolomite. To obtain mixed oxides, dolomite samples were prepared via calcination in a quartz cylindrical furnace under an ambient atmosphere at 900 °C, and subsequently thermally pre-treated under an inert (argon) stream at 650 °C. Characterization of the as-prepared samples involved morphological, structural, textural, and optical features examined through XRD, BET, SEM-EDS, FT-IR, and RAMAN, XPS, and UV-vis spectroscopy, whereas TGA and subsequent multicyclic tests were used to study the CO2 sorption. The dolomite sample calcined at 900 °C for 60 min, and after being activated under an inert atmosphere (argon), labeled PCD60Act, exhibited the highest CO2 uptake of 0.477 gCO2/gsorbent; after 15 sorption–regeneration cycles, it still retained a CO2 uptake of 0.38 gCO2/gsorbent at 650 °C, and it was also successfully regenerated at this moderate temperature, demonstrating 84% capture capacity retention. These remarkable results are explained by the crystalline defects generated during the thermal pre-treatments of the dolomite. This research offers valuable perspectives on the viability of employing thermally pre-treated dolomite as an inexpensive, thermally stable, and moderate-temperature regenerable CaO-based sorbent for applications in CO2 removal in the context of integrated carbon capture and conversion (ICCC) for the production of high-purity hydrogen.